PKM kepada Mitra Bisnis Rafiza Fried Chiken di Wilayah Depok, Jawa Barat (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2020)
Marketing is one of the important things that must be done when running a business, both new businesses and old businesses that have been initiated for years. Before running marketing, the first thing to do is determine the marketing concepts and marketing strategies that are effective in selling products. With the number of small businesses that are emerging at this time, it is necessary to have an appropriate marketing strategy in order to attract the interests of consumers. Even though it is difficult, but if the focus is on planning the marketing strategy, it is not impossible that small businesses can grow to become large, while the abdimas here are more focused on SME fast food fried chicken franchise in Depok, West Java. Depok area is a densely populated location, where many migrants who come from other regions then settle there. Due to the large number of residents who come from various regions, it provides a great opportunity for traders to open their shanties and look for profits there. As a result of the many traders who participate in selling there, it creates a fierce competition in building their businesses.